An Analysis of The Influence of Aggregate Expenditure Regional Gross Domestic Product Growth In The Lampung Province - H.M. A. Subing (Bandar Lampung University, 2015)
This research is intended for analyzing the influence of aggregate expenditure involving consumption, investment, governmental expenditure, and net export on the growth of Gross Regional Domestic Product in Lampung Province. The research was conducted in six monthsincluding design, implementation and reporting on result of the research.The research is conducted through library study and data is obtained from the Central Bureau of Statistics, Bank Indonesia Regional Research and Development Agency, BAPPEDA. Data consist of aggregate expenditure, economic growth. This research uses the methodology of explanatory research with quantitative analysis technique by applying statistic model of causality through double linear regression analysis with the significance of five percent.Result of research indicates that the aggregate expenditure; consumption expenditure investment, governmental expenditure and net export have a simultaneous effect on the growth of PDRB. Partially, the PDRB growth is more positively affected household consumption expenditure, and private investment.